2019
DOI: 10.1080/00958964.2019.1598927
|View full text |Cite
|
Sign up to set email alerts
|

How many young generations are there? – A typology of teenagers’ climate change awareness in Germany and Austria

Abstract: Under the premise that the young generation of teenagers cannot be considered to be uniform, this study identified groups of teenagers based on their level of climate change awareness. Questionnaires answered by 760 teenagers (13-16 years old) from Germany and Austria were analyzed using a hierarchical cluster analysis. The teenagers were assigned to four groups that differed as to their cognitive, affective and conative aspects of climate change awareness. Based on the empirical results, the authors argue tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 46 publications
2
36
0
7
Order By: Relevance
“…(2019) revealed that concern had an insignificant effect on environmental behaviour. Kuthe et al (2019) also showed that concern about climate change is not always related to willingness to act climate friendly among teenagers. However, in this paper as in previous our research (Liobikiene and Juknys, 2016), we expected perception of environmental problems to have a positive impact on pro-environmental behaviour.…”
Section: Value-belief-norm Theory Analysing the Determinants Of Pro-ementioning
confidence: 99%
“…(2019) revealed that concern had an insignificant effect on environmental behaviour. Kuthe et al (2019) also showed that concern about climate change is not always related to willingness to act climate friendly among teenagers. However, in this paper as in previous our research (Liobikiene and Juknys, 2016), we expected perception of environmental problems to have a positive impact on pro-environmental behaviour.…”
Section: Value-belief-norm Theory Analysing the Determinants Of Pro-ementioning
confidence: 99%
“…Luchs and Mooradian (2012) reported that adults are more likely to act sustainably, while Y. Lee et al (2019), Kuthe et al (2019), and Sinnappan and Abd Rahman (2011) highlighted that young educated consumers significantly engage in sustainable consumption as they are now more aware of environmental issues and their potential impact on the environment. In agreement, Stevenson et al (2017) highlighted that adolescents whose parents are well-educated, with a high socioeconomic status, could be more interested regarding sustainable and environmental development.…”
Section: Demographics Variablesmentioning
confidence: 99%
“…As noted, this research highlights the environmental perceptions of different generations of citizens in Spain regarding climate change in the digital society. Unlike other recent studies, this article's attraction or novelty lies in the fact that this empirical analysis is carried out from the perspectives of awareness, human action, and self-responsibility [61,62]. Perhaps, this phenomenon -the difficulty of reaching the different generations with the same initiatives from this perspective-, together with other reasons of an eco-political nature, hinders the implementation of new models of governance based on sustainable development, green economy, and social happiness by the top management of public administrations [63].…”
Section: Discussionmentioning
confidence: 99%